Antibacterial and antioxidant activities of banana (Musa paradisiaca cv. Mysore) inflorescence, a banana by-product - Birdie Scott Padam (2012)
The purpose of this study was to determine the factors influencing personal financial management practices among Generation Y in Malaysia with the moderating role of future orientation. In this study, the independent variables were financial literacy, parents, peers, mass media, money attitude of power-prestige, money attitude of retention-time, money attitude of distrust and money attitude of anxiety) while personal financial management practices act as the dependent variable. Besides, future orientation serves as a moderator. This study adapted the Theory of Planned Behaviour as an underpinning theory to predict and understand the factors that influence personal financial management practices among Generation Y in Malaysia. Samples for the study were collected from the states of Sabah, Sarawak, Selangor, Kuala Lumpur, Johor, and Penang. The participants for this study were individuals who were born between 1981 to 2001 and had any loan or credit card. A total of 205 valid questionnaires were used for the analysis carried out in this study. Data were analyzed using the Structural Equation Modelling (SEM) technique using Partial Least Squares (PLS). Results from the analyzed data revealed that only financial literacy, peers, mass media, money attitude of retention-time, money attitude of distrust and money attitude of anxiety positively influence the personal financial management practices of Generation Y in Malaysia. It also showed that future orientation only plays a moderating role in the relationship between financial literacy and money attitude of distrust towards personal financial management practices. The future orientation strengthens the relationship between financial literacy and money attitude of distrust and personal financial management practices among Generation Y in Malaysia. The study’s outputs may serve as guidelines by the Malaysian government agencies and policymakers, apart from extending the body of knowledge to shed some light on personal financial management practices. The findings of the study also offer an alternative approach in addressing the escalating bankruptcy issues faced by Generation Y in Malaysia.